(untitled) (Research, Society and Development, 2023)
This study aims to present an assessment of the environmental integrity along the Ariaú River, Amazonas State, based on six sampling points, using the Rapid River Assessment Protocol (PAR,) that combine qualitative and semi-quantitative procedures to assessment of river systems. An analysis of physical and chemical variables of the water was also carried out at points located in the river and in branches of the river. The environmental assessment was carried out by undergraduate students and covered 15 PAR parameters and 9 water quality parameters. The data indicates that the river evaluated stretches have good and excellent environmental integrity and the water quality values are in accordance with those established by current standards. Therefore, it is extremely important from environmental use and conservation point of view to monitor and maintain the natural characteristics of the Ariaú River, as it is recognized for its potential for implementing several socioeconomic activities, such as the ecological tourism.